Perbaikan Pertumbuhan dan Pengendalian Penyakit Busuk Pangkal Batang Bawang Putih dengan Aplikasi Pupuk Kohe Kambing yang Difermentasi dengan Bioaktivator Streptomyces sp - Irwan Muthahanas; M. Taufik Fauzi; Bambang Supeno; Nurrachman Nurrachman; Hery Haryanto (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2025)
This research is an experimental study conducted on rice fields owned by farmers in Sembalun village and the Microbiology Laboratory of the Faculty of Agriculture at Unram. The research aims to determine the effect of fertilizer fermented with Streptomyces sp. on the growth and yield of garlic plants as well as the control of basal rot disease in garlic plants. The research was arranged using a Completely Randomized Design (CRD) consisting of 6 treatments and repeated 6 times, resulting in 36 experimental units. The six treatments are: Without fertilizer application (P0), Goat manure fertilizer without the addition of bioactivator (P1), Goat manure fertilizer + Streptomyces sp. isolate SH (P2), Goat manure fertilizer + Streptomyces sp. isolate BSi (P3), Goat manure fertilizer + Streptomyces sp. isolate BSc (P4). Goat manure fertilizer + Isolate SH + Liquid SH (P5). The research results show that the treatment with Streptomyces sp isolate BSi (P3) produced the tallest plants (57.741 cm) and was significantly different from the treatment without fertilizer. (P0). Treatment P3 also produced the highest number of leaves (10.05) significantly different from the other treatments. The highest wet and dry weight of garlic bulbs was obtained in treatment P5, which were 2.556 g and 2.343 g, respectively. The lowest intensity of Fusarium wilt disease was obtained in treatment P4, which was 6.33%, and it was significantly different from P0 or without fertilizer treatment.